OPTIMIZING THE COMPONENTS OF HYBRID RYE GROWING PRACTICE IN POLISSIA - Moisiienko, V. V.; Тymoshchuk Т. M.; Nazarchuk, O. P.; Diakov, T. V. (Scientific Progress & Innovations, 2021)
The genetic potential of new winter rye hybrids can be implemented by optimizing their growing practice technology. The paper shows the results of yield estimation of F1 hybrid of winter rye Helltop in comparison with Zabava variety. The impact of sowing time on the peculiarities of yield formation of hybrid winter rye as well as on grain quality indicators under the conditions of Polissia has been studied. It has been established that the crop capacity of hybrid F1 of winter rye Helltop significantly exceeded that of Zabava variety, the average yield of which during the years of research made 5.7 t/ha, the grain yield gain equaled 2.2 t/ha. The mid-term of sowing (8th–15th of September) was the best one, as it provided the maximum yield of the hybrid winter rye grain – 5.7 t/ha. Under the early sowing time (1st–7th of September,) this indicator was by 12.3 % lower and under the late sowing time (16th–20th of September) it was by 29.8 % lower. Herewith, the grain quality of the hybrid rye changed significantly. Thus, the largest thousand-grain weight – 45 g and the grain hectoliter weight – 735 g were registered under a mid- sowing time. Spraying with Chlormequat-chloride and Medax Top retardants at the beginning of the plant leaf-tube forming (ВВСН 30–32) favored the decrease of the plant height by 26–28 % and the lodging of the hybrid rye by 20 %. Double spraying of Helltop F1 winter rye hybrid with Medax Top retardant at the stages of ВВСН 30–32 and 37–39 decreased the plant height by 44 % and the lodging of the hybrid rye by 90 % as compared with the control. The application of retardants at the stage of ВВСН 30–32 increased the grain yield by 1.5– 1.7 t/ha as compared with the control. The maximal grain yield (5.7 t/ha) was received under double spraying of Helltop F1 hybrid rye plants with Medax Top morpho-regulator at the stages of ВВСН 30–32 and ВВСН 37–39, which was 2.2 t/ha higher as compared with the control.